2020
DOI: 10.3390/toxins12010027
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Induced Activity and Folding of a Repeat in Toxin Lipase from Antarctic Pseudomonas fluorescens Strain AMS8

Abstract: It is hypothesized that the Ca2+ ions were involved in the activity, folding and stabilization of many protein structures. Many of these proteins contain repeat in toxin (RTX) motifs. AMS8 lipase from Antarctic Pseudomonas fluorescens strain AMS8 was found to have three RTX motifs. So, this research aimed to examine the influence of Ca2+ ion towards the activity and folding of AMS8 lipase through various biophysical characterizations. The results showed that CaCl2 increased lipase activity. The far-UV circular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
1
6
0
1
Order By: Relevance
“…Experimental data on the effect of CaCl 2 on the AMS8 lipase activity supported the idea that Ca 2+ ions contributed to the enzyme structural stability [14]. Far-UV CD spectra revealed that the presence of CaCl 2 improved the secondary structure of AMS8 lipase.…”
Section: Root Mean Square Fluctuation (Rmsf) Value Of Residue Analysismentioning
confidence: 66%
See 2 more Smart Citations
“…Experimental data on the effect of CaCl 2 on the AMS8 lipase activity supported the idea that Ca 2+ ions contributed to the enzyme structural stability [14]. Far-UV CD spectra revealed that the presence of CaCl 2 improved the secondary structure of AMS8 lipase.…”
Section: Root Mean Square Fluctuation (Rmsf) Value Of Residue Analysismentioning
confidence: 66%
“…The lower the value of the k D , the higher the ligand's binding affinity to AMS8 lipase. If the k D value was high, the ligand would be weakly bound to the protein (other target molecules) [14]. Even though the unit measurement was used in the laboratory experiment (ITC) and the in silico study (molecular docking) was different due to the different modes of analysis, both analyses gave the same target, which focused on the binding affinity between the ligand (Ca 2+ ) and protein structure (AMS8 lipase).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it is clear that calcium-mediated conformation changes of the repeats play an important role in target cell recognition and in membrane-activity of certain RTX toxins [13,17]. This is not only the case for pore formation of cytolytic RTX toxins but also for the AMS8 lipase from the Antarctic Pseudomonas fluorescens strain AMS8 [23]. The three RTX motifs of this protein react to the presence of calcium ions.…”
mentioning
confidence: 99%
“…The three RTX motifs of this protein react to the presence of calcium ions. The tightly bound calcium results in an increase of lipase activity together with changes in its secondary structure [23].…”
mentioning
confidence: 99%